PENGARUH PENERAPAN MARKETING SYARIAH, KEPUASAN NASABAH DAN KEPERCAYAAN NASABAH TTERHADAP LOYALITAS NASABAH PADA BPRS BUMI RINJANI KEPANJEN MALANG - Fetty Rahayu Sri Mulyani; Muhammad Hufron; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRAKThe development of financial institution of both bank anda non-bank based onsharia service trhives in Indonesia.In this case of course required he existence ofresearch to analyze the influence of implemetation shaia marketing, customersatisfaction and customer trust on loyalty.the number of respondents in this studywas 99 by using saccidental samplinh technique and using statistica anilysis toolSPSS. the result of the analysis show that partially have a negative relathionthipand not significant but in general respondents agree with the indicator on thevariable. Simultaniously have a positive and significant relathionship.Keyword : Sharia Marketing, Customers, Customers Satisfaction, Cutomer Trust